2009
DOI: 10.1158/1541-7786.mcr-08-0360
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Oxygen Concentration Enhances the Stem-Like Properties of CD133+ Human Glioblastoma Cells In vitro

Abstract: In vitro investigations of tumor stem-like cells (TSC) isolated from human glioblastoma (GB) surgical specimens have been done primarily at an atmospheric oxygen level of 20%. To determine whether an oxygen level more consistent with in situ conditions affects their stem cell–like characteristics, we compared GB TSCs grown under conditions of 20% and 7% oxygen. Growing CD133+ cells sorted from three GB neurosphere cultures at 7% O2 reduced their doubling time and increased the self-renewal potential as reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
201
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(212 citation statements)
references
References 48 publications
(74 reference statements)
10
201
0
1
Order By: Relevance
“…Recent studies have suggest that cancer stem cells of several tumor types have similar redox patterns to normal stem cells (Kobayashi et al, 2012). Consistent with the present study, hypoxia enhances the expression of stemness genes such as Sox2 and Oct4 in glioblastoma (McCord et al, 2009). Furthermore, it has been shown that HIF-1α interacts with Notch under hypoxic conditions to maintain a stem cell phenotype and Notch signaling is enhanced by hypoxia (Gustafsson et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have suggest that cancer stem cells of several tumor types have similar redox patterns to normal stem cells (Kobayashi et al, 2012). Consistent with the present study, hypoxia enhances the expression of stemness genes such as Sox2 and Oct4 in glioblastoma (McCord et al, 2009). Furthermore, it has been shown that HIF-1α interacts with Notch under hypoxic conditions to maintain a stem cell phenotype and Notch signaling is enhanced by hypoxia (Gustafsson et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…While brain tumor stem cells have been linked to a perivascular niche, we have found an additional enrichment of GSCs around necrotic regions that often display hypoxic condition . Several groups have found that restricted oxygen promotes a GSC phenotype (McCord et al, 2009;Soeda et al, 2009). Our group also found that restricted oxygen conditions increase expression of GSC markers and the indicators of self-renewal, suggesting that the state of cancer stem cell may be plastic and that microenvironmental conditions can promote the acquisition of a stem cell-like phenotype (Heddleston et al, , 2010.…”
Section: Hypoxic Responses In Glioblastoma Stem Cellssupporting
confidence: 67%
“…Interestingly, HIF-1α and HIF-2α specifically controlled VEGF expression in GSCs in a nonredundant manner ). In addition, hypoxia can promote the expansion of GSC fraction and regulate expression of stem cell markers McCord et al, 2009;Soeda et al, 2009). Thus, hypoxia may enhance tumor progression and therapeutic resistance through its promotion of a cancer stem cell phenotype and induction of VEGF and other pro-angiogenic factors.…”
Section: Glioblastoma Stem Cells and Tumor Angiogenesismentioning
confidence: 99%
“…In MDA-MB-231 cells, miR-495 upregulation hindered REDD1 induction and allowed cells to proliferate continuously in a hypoxic environment (Figure 4). Short-term (48 h) culture in hypoxia has been shown to expand the sub-population of cells expressing CSC marker CD133 (Soeda et al, 2009), and to enhance the stem-like phenotypes (McCord et al, 2009). Although most studies have focused on the roles of hypoxia-inducible factors in inducing CSC phenotypes and conferring tumorigenic potential (Covello et al, 2006;Heddleston et al, 2009), our data, in contrast, demonstrate the role of miR-495 promoting cell proliferation in hypoxia.…”
Section: E12 and E47 Activate The Expression Of Mir-495mentioning
confidence: 46%